DEVELOPMENT AND EVALUATION OF PEPEROMIA PELLUCIDA L. PEEL-OFF GEL MASK AS ANTI-ACNE AGENT - Indra, Indra; Yadi Aditya, Prawira; Fajar, Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
This study investigates the development of a peel-off gel mask formulated with Peperomia pellucida L. extract as a natural treatment for acne. Peperomia pellucida L., traditionally valued for its medicinal properties, was characterized microscopically and macroscopically to confirm the plant’s identity and quality. Ethanol extraction yielded 16.54% bioactive compounds, including flavonoids, tannins, saponins, and triterpenoids, known for their antibacterial and anti-inflammatory activities. The research utilized a concentration-dependent approach, formulating three gel variants with 5% (F1), 10% (F2), and 15% (F3) extract concentrations. Antibacterial testing against Propionibacterium acnes showed that F3 exhibited the largest inhibition zone (10.72 mm), significantly outperforming the positive control (4.6 mm). Stability testing revealed that the formulations maintained consistent color, odor, and pH but faced challenges in viscosity and homogeneity at extreme temperatures. Hedonic testing indicated that participants favored F2 (10% extract) for its balanced aroma, color, and ease of application, although F1 and F3 were preferred for texture. Despite stability challenges, the formulations, mainly F3, demonstrated promising antibacterial efficacy. In conclusion, the peel-off gel mask containing Peperomia pellucida L. extract (F3) shows significant potential as a natural alternative to synthetic acne treatments. Further refinement is needed to enhance stability and user experience while maintaining its high antibacterial activity. study explores the development of a peel-off gel mask formulated with Peperomia pellucida L. extract for acne treatment. Peperomia pellucida L., traditionally known for its medicinal properties, was characterized microscopically and macroscopically, confirming the plant’s identity and quality. The ethanol extraction process yielded 16.54% of bioactive compounds, including flavonoids, tannins, saponins, and triterpenoids, known for their antibacterial and anti-inflammatory properties. Phytochemical screening confirmed these compounds’ presence, and antibacterial testing against Propionibacterium acnes revealed concentration-dependent inhibition, with the highest inhibition zone observed in the 15% extract formulation (F3). The gel formulations were evaluated for physical properties, stability, and user acceptance. Stability testing demonstrated consistency in colour, odour, and pH but revealed challenges in inhomogeneity and viscosity at extreme temperatures. Despite these issues, the formulations maintained antibacterial efficacy, mainly F3. Hedonic testing showed that participants favored F2 (10% extract) for its balanced aroma, color, and ease of application, although F1 and F3 were preferred for texture. In conclusion, the peel-off gel mask containing Peperomia pellucida L. shows significant potential as a natural, effective treatment for acne. However, further refinement is needed to optimize stability and user-friendliness while maintaining high antibacterial efficacy. These findings suggest that the extract could be a valuable addition to topical acne treatments, offering a natural alternative to synthetic products